Flora das cangas da Serra dos Carajás, Pará, Brasil: Celastraceae - Lombardi, Julio Antonio [UNESP]; Biral, Leonardo [UNESP] (FapUNIFESP (SciELO), 2016)
This study presents the species of Celastraceae registered for the cangas of Serra dos Carajás, Pará state, including morphologic descriptions, illustrations, and comments. Four species were found in the region: Anthodon decussatum, liana widely distributed in the Neotropics; Cheiloclinium hippocrateoides, liana restricted to Amazon basin; Maytenus guyanensis, shrub or tree widely distributed in the Neotropics; and Tontelea laxiflora, liana occurring in the Amazon basin and northeastern Brazil.
Flora of the cangas of the Serra dos Carajás, Pará, Brazil: Celastraceae
Keywords: Celastroideae; FLONA Carajás; Flora; Hippocrateoideae; Salacioideae; Taxonomy